Coping practices and the spatial dimension of authority design - Constantin Kaplaner; Yves Steinebach (Public Administration Review, 2023)
Frontline implementers develop coping practices to deal with implementation burdens. Unfortunately, we have only limited knowledge of how widespread and systematic these practices are applied. This paper provides a comprehensive analysis of the enforcement activities carried out in the context of the European Union Industrial Emission Directive, relying on a quantitative data set that summarizes the information from more than 2000 inspection reports published by the German state Baden-Württemberg. Our analysis reveals that inspectors tend to give priority to sites that (1) are closer and easier to reach and (2) that pose only a small risk to their environment. These findings indicate that implementers are primarily guided by concerns over the quantitative rather than the qualitative aspects of their work. These insights highlight that public authorities' spatial location is a crucial, yet still unexplored factor in the study of policy implementation.
Keywords: 340